Criminalization Arrangements for Corporations (Comparative Study of Indonesia and Australia) - Muhammad Iqbal Baiquni; Septhian Eka Adiyatma; Atha Difa Saputri; Riki Julianto; Ridwan Arifin; Nurul Fibrianti (Universitas Negeri Semarang, 2023)
This research was conducted on corporate criminal liability arrangements in Indonesian legislation, with the long-term goal of harmonization of corporate criminal liability arrangements, so as to realize certainty, expediency and legal justice in law enforcement in Indonesia. To support the realization of harmonization in corporate criminal liability arrangements in the legislation, it is necessary to review corporate criminal liability arrangements in other countries, both those with the same legal system as Indonesia and with countries with a common law system, namely Australia. The research method used to achieve the research goals and targets is normative legal research with a statutory, and comparative approach method. The projected results of this study are in the form of real data on the implementation of corporate penal regulations for the National Legal System. The output of this research is in the form of published articles in accredited national journals